Efficacy and Safety of Transcranial Magnetic Stimulation for Attention‐Deficit Hyperactivity Disorder: A Systematic Review and Meta‐Analysis - Binbin Fu; Xiangyue Zhou; Xuan Zhou; Xin Li; Zhengquan Chen; Yanbin Zhang; Qing Du (Brain and Behavior)
ABSTRACT Background Transcranial magnetic stimulation (TMS) is a promising neuromodulation technique that has been widely used in neuropsychiatric disorders, but there was no evidence on its effect on the improvement attention‐deficit hyperactivity disorder (ADHD). Objective This systematic review and meta‐analysis aimed to investigate the efficacy and safety of TMS in reducing ADHD symptoms. Method We systematically searched four databases (PubMed, Embase, Web of Science, and Cochrane Library databases) for randomized controlled/crossover trials on the efficacy and safety of TMS on ADHD symptom improvement compared to sham rTMS or non‐TMS interventions, published until September 18, 2024. Extracted data from the included studies involved patient characteristics, intervention protocols, and main outcomes. The effect size of the TMS treatment was evaluated using the standardized mean difference (SMD) with a 95% confidence interval (CI), calculated with either a random effects model or fixed effects model depending on the level of heterogeneity. Result Eight studies (325 ADHD patients in total) were included in this systematic review and meta‐analysis. According to the core symptoms, TMS significantly improved inattention (SMD = −0.94, 95% CI = −1.33 to −0.56, p < 0.001) and hyperactivity/impulsivity (SMD = −0.98, 95% CI = −1.27 to −0.69, p < 0.001) compared to non‐TMS interventions after 3–6 weeks of intervention. During the 1‐month follow‐up, the TMS group still demonstrated a significant improvement in inattention symptoms compared to the non‐TMS group (SMD = −0.67, 95% CI = −1.06 to 0.28, p < 0.001). The total symptoms in the TMS group only showed improvement in the 1‐month follow‐up compared to the non‐TMS group. (SMD = −0.48, 95% CI = −0.82 to −0.14, p = 0.005). Only minor adverse events were reported in the included studies, comprising headache and scalp discomfort. Conclusion TMS significantly improved the inattention, hyperactivity/impulsivity, and total symptom scores in ADHD patients with minor adverse events. Future research should focus on the association between different brain regions and symptoms in ADHD patients, which is crucial for stimulation navigation in TMS interventions. The trial is registered in PROSPERO (PROSPERO registry number: CRD42023473853).